Electrical conductivity and optical properties of a new synthesized poly(tetramethylene ethylene diamine) polymer organic semiconductor - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz; Farooq, W. A. (Natl Inst Optoelectronics, 2011)
Electrical conductivity and optical properties of poly(tetramethylene ethylene diamine) polymer have been investigated. The electrical conductivity of the polymer increases with increase of temperature. The Arrhenius conductivity curve of the polymer shows the linear and non-linear regions. The non-linear behavior of the polymer confirms the ionic conductivity behavior analyzed by the Vogel-Tamman-Fulcher (VTF) theory. The room temperature conductivity of the poly(tetramethylene ethylene diamine) polymer was found to be 2.56x10(-8) S/cm. The optical band gap of the polymer was analyzed by optical absorption spectra and was found to be 4.15 eV with direct optical transition. The refractive index of the polymer was analyzed by the Single oscillator model. The oscillator energy E(0), dispersion energy E(d), and long wavelength refractive index n(infinity) values of the polymer were found to be 9.69 eV, 31.36 eV and 2.05, respectively. The obtained electrical and optical results indicate that the poly(tetramethylene ethylene diamine) polymer is a organic semiconductor with calculated electrical and optical parameters.
Keywords: Organic semiconductor; Polymer; Electrical properties